Failure of the Emergency Generator Start-Stop Working System on the AHTS Logindo Sturdy Ship: Kegagalan Sistem Kerja Start-Stop Emergency Generatordi Kapal AHTS Logindo Sturdy - Sultan; Abiyyu, Muhammad Faris Abid; Kurniawan, Dedi; Nurmala, Eka; Muda, Indra (PT. Alpha Trianguli Australis, 2024)
An emergency generator is a backup generator that is used only for emergencies. When the ship operates normally, the generator is on stand-by or ready to be activated at any time. During an emergency, such as when the ship experiences damage that causes the main propulsion power source, auxiliary machinery, and other equipment to stop operating due to a lack of electricity supply from a failure in the electrical system, the emergency generator system is needed to replace the function of the ship's main generator. This research uses descriptive qualitative methods. The results of this research can be summarized as follows: 1) The implementation of work safety on ships is considered less than optimal; 2) The implementation of work safety significantly influences the mentality and quality of work; and 3) Supervision activities on board the ship are carried out through safety meetings.